ACTIVITY TEST OF ALOE VERA PEEL EXTRACT (ALOE VERA) GEL WITH RABBIT’S (Orycctolagus Cuniculus) COMBUSTIO (MINOR BURNS) - Yusuf, Anna Lesmanasari; Nugraha, Davit; Wahlanto, Panji; Indriastuti, Marlina; Lestari, Nina Indri (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2020)
Background: Aloe vera skin plants contain lots of flavonoids, tannins, saponins, polyphenols and steroids. Aloe vera is known to be efficacious as boils, bruised skin, chapped, blisters, hair loss, hemorrhoids, sore throat and can treat conbustio. Sticky material found in the of aloe vera peel can prevent infection in burns. Sticky material found in the skin of aloe vera can prevent infection in combustio. In the past, the use of aloe vera peel as a medicine for combustio is by applying a slimy leaf to the wound until the mucus covers the entire wound. Aloe vera peel to heal combustio can be facilitated by making dosage forms such as gel. Gel is usually used as a drug for the topical . Objectives This study aims to determine the effect of aloe vera peel extract gel on healing combustio (minor burn) in rabbits. Methods This research is an experimental laboratory study, tested on rabbit combustio(minor burn). Results: Healing combustio formulation of aloe vera peel extract 5% as much as 90%, the formulation of aloe vera extract 10% as much as 93.3% and the formulation of aloe vera peel extract 15% as much as 86.7%. Conclusions and suggestions: : Aloe vera peel extract gel formulation with 5%, 10% and 15% concentration can accelerate the drying of combustio (minor burns). It is recommended to test with other dosage forms such as ointments, lotion or creams.